2023
DOI: 10.3390/medicina59030551
|View full text |Cite
|
Sign up to set email alerts
|

The HIT Study—The Hydroxychloroquine Effect in the Treatment of Patients with Age-Related Macular Degeneration: A Randomized Controlled Trial

Abstract: Background and Objectives: Decreased age-related macular degeneration (AMD) has been reported in individuals with rheumatoid arthritis treated with hydroxychloroquine (HCQ, plaquenil). Materials and Methods: In a randomized controlled trial with a parallel study design, we assessed visual acuity, central macular thickness measured with macular optical coherence tomography (OCT), and the number and size of drusen, following treatment with HCQ or a placebo in individuals with AMD. The patients received a daily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…McGeer and Sibley initially reported that their patients with RA, following treatment with HCQ, were relatively spared from the development of AMD [ 16 ], suggesting a potential protective effect of HCQ against AMD. Yahalomi’s study found that patients undergoing HCQ treatment experienced slower progression of AMD and fewer formations of vitreous drusen [ 17 ]. However, the overall effectiveness and mechanism of action of these treatments in this context remain.…”
Section: Introductionmentioning
confidence: 99%
“…McGeer and Sibley initially reported that their patients with RA, following treatment with HCQ, were relatively spared from the development of AMD [ 16 ], suggesting a potential protective effect of HCQ against AMD. Yahalomi’s study found that patients undergoing HCQ treatment experienced slower progression of AMD and fewer formations of vitreous drusen [ 17 ]. However, the overall effectiveness and mechanism of action of these treatments in this context remain.…”
Section: Introductionmentioning
confidence: 99%
“…HCQ-induced retinal toxicity has been reproduced in several animal species, including rats, cats, dogs, rabbits, pigs, and monkeys. An interesting hypothesis was recently proposed stating that HCQ could even have the effect of preventing age-related macular degeneration (ARMD) in subjects with rheumatoid arthritis [ 4 ]. ARMD is the most common cause of blindness in the elderly population, and local chronic inflammation plays a role in the pathogenesis and progression of this disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%